Strauss and Mayer's emergency department management - Strauss, Robert W.; Mayer, Thom A. (McGraw-Hill Education Medical, 2014)
Offers a real-world, pragmatic guide designed to help emergency department managers efficiently which handle the many complex issues that arise in this challenging clinical environment. This title delivers practical solutions to virtually any problem that may arise in running an emergency department or acute care center.